Pengalaman Perilaku Seks Pranikah Remaja Putri di Kota Garut - Tanti Suryawantie; Kurniawan Dewi Budiarti; Luqy Luqman Effendy (Jurnal Medika Cendikia, 2016)
Teenager have a many problems, one of the most prominent is premarital sexual behavior. Premarital sexual behavior is likely to undermine the future of youth, especially young women. This study to explore the experience of premarital sexual behavior of young women in the city of Garut. This study is a qualitative research with phenomenological approach. The respondence were five people with a lifespan of 15-18 years. The data collected by recordings obtained through in-depth interviews. This study identified four themes, such as: 1) the initial experience of young women perform premarital sexual behavior 2) premarital sexual behavior of young women 3) motif girls perform premarital sexual behavior 4) the impact of premarital sexual behaviors in adolescent girls. The results of this study are expected to provide an overview premarital sexual behavior in adolescent girls, particularly for health care providers to provide information giving sexual problems, and society is increasing social control, so that teens can improve sexual and reproductive health.